2020
DOI: 10.3390/plants9060701
|View full text |Cite
|
Sign up to set email alerts
|

Salt Distribution and Potato Response to Irrigation Regimes under Varying Mulching Materials

Abstract: Water scarcity and frequent drought spells are becoming critical challenges to sustainable agricultural development, especially in arid and semiarid regions. Thus, this work aims to investigate the effect of deficit irrigation and varying mulching materials on soil moisture content, salt distribution, and potato yield. The experiment consisted of three irrigation regimes (I100%, I80%, and I60%) of crop evapotranspiration (ETc), designated as I100%, I80%, and I60% of ETc, and five mulching treatments viz. (i) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…In this experiment, compared with the output in CK, mild (WD3) and moderate (WD7) regulated de cits in the tuber enlargement stage signi cantly decreased the output by 20.86% and 26.50%, respectively. Consistent with this study, Mustafa Ünlü et al 38 , Hassan et al 39 , Nagaz et al 40 , and Im et al 41 also found that water de cit at the tuber enlargement stage reduces production by approximately 20% compared with that with a su cient water supply. As tubers begin to divide and expand in the tuber enlargement stage, potatoes transition from the reproductive stage to the vegetative growth stage.…”
Section: Discussionsupporting
confidence: 73%
“…In this experiment, compared with the output in CK, mild (WD3) and moderate (WD7) regulated de cits in the tuber enlargement stage signi cantly decreased the output by 20.86% and 26.50%, respectively. Consistent with this study, Mustafa Ünlü et al 38 , Hassan et al 39 , Nagaz et al 40 , and Im et al 41 also found that water de cit at the tuber enlargement stage reduces production by approximately 20% compared with that with a su cient water supply. As tubers begin to divide and expand in the tuber enlargement stage, potatoes transition from the reproductive stage to the vegetative growth stage.…”
Section: Discussionsupporting
confidence: 73%
“…However, when the SSI irrigation technique was combined with BPE soil mulch under the DI regime, it was found to be the most effective in conserving irrigation water. This combination not only mitigated the negative effects of the DI regime but also promoted plant health and improved water productivity (Abdelhady et al, 2017;Chen et al, 2018;Abd El-Wahed et al, 2020;Sang et al, 2020).…”
Section: Effect Of Irrigation Scheduling Irrigation Technique and Soi...mentioning
confidence: 99%
“…Mulching soil with either organic materials or black polyethylene sheets, even though the black polyethylene sheets are more effective than organic materials, reduces evaporation, retains soil moisture, decreases the effect of ambient temperature on soil temperature, and suppresses weed growth. These all can support better vegetative growth and overall plant health (Abdelhady et al, 2017;Chen et al, 2018;Abd El-Wahed et al, 2020;Sang et al, 2020).…”
Section: Tomato Plants' Vegetative Measurementsmentioning
confidence: 99%
“…The high light transmission increased soil temperature and created a microclimate conducive to weed germination (Rajablariani et al, 2015). Tomato (Solanum lycopersicum), a solanaceous crop, is the most important horticultural crop in the world (Schwarz et al, 2014;Bhandari et al, 2017), and ranks first among all vegetable crops farmed in Egypt (El-Wahed et al, 2020). It is well adapted to its soil and climate conditions and grown all year round (Shamshiri et al, 2018).…”
Section: Introductionmentioning
confidence: 99%